Synthesis of New Bis(spiro-β-lactams) via Interaction of Methyl 1-Bromocycloalcanecarboxylates with Zinc and N,N′-Bis(arylmethylidene)benzidines - N. F. Kirillov; E. A. Nikiforova; D. V. Baibarodskikh; T. A. Zakharova; L. S. Govorushkin (Journal of Chemistry)
Interaction of the Reformatsky reagents, prepared from methyl 1-bromocyclopentane-1-carboxylate or methyl 1-bromocyclohexane-1-carboxylate, with N,N′-bis(arylmethylidene)benzidines has given rise to a set of intermediates as a result of nucleophilic addition to the C=N group of a substrate. Further intramolecular attack of the amide nitrogen atom onto the ester carbonyl group is responsible for the ring closure, which affords two series of spirocompounds: 2,2′-([1,1′-biphenyl]-4,4′-diyl)bis(3-aryl-2-azaspiro[3.4]octan-1-one) or 2,2′-([1,1′-biphenyl]-4,4′-diyl)bis(3-aryl-2-azaspiro[3.5]nonan-1-ones).